Personalized treatment options for thyroid cancer: current perspectives - Khatami F; Larijani B; Nikfar S; Hasanzad M; Fendereski K; Tavangar SM (Dove Medical Press, 2019)
Fatemeh Khatami,1 Bagher Larijani,2,3 Shekoufeh Nikfar,3,4 Mandana Hasanzad,3,5 Kiarad Fendereski,6 Seyed Mohammad Tavangar1,7 1Chronic Diseases Research Center, Endocrinology and Metabolism Population Sciences Institute, Tehran University of Medical Sciences, Tehran, Iran; 2Endocrinology and Metabolism Research Center, Endocrinology and Metabolism Clinical Sciences Institute, Tehran University of Medical Sciences, Tehran, Iran; 3Personalized Medicine Research Center, Endocrinology and Metabolism Clinical Sciences Institute, Tehran University of Medical Sciences, Tehran, Iran; 4Department of Pharmacoeconomics and Pharmaceutical Administration, Faculty of Pharmacy, Tehran University of Medical Sciences, Tehran, Iran; 5Medical Genomics Research Center, Tehran Medical Sciences, Islamic Azad University, Tehran, Iran; 6Pediateric Urology and Regenerative Medicine Research Center, Children’s Medical Center, Tehran University of Medical Sciences, Tehran, Iran; 7Department of Pathology, Dr. Shariati Hospital, Tehran University of Medical Sciences, Tehran, IranCorrespondence: Seyed Mohammad TavangarDepartment of Pathology, Dr. Shariati Hospital, Tehran University of Medical Sciences, Jalale Ale Ahmad Ave, Tehran, IranTel +98 218 490 2187Fax +98 218 863 3078Email Tavangar@ams.ac.irAbstract: Thyroid cancer is one of the most common endocrine malignancies, with increasing incidence all over the world. In spite of good prognosis for differentiated thyroid carcinoma, for an unknown reason, about 5–10% of the patients, the cancer will show aggressive behavior, develop metastasis, and be refractory to treatment strategies like radioactive iodine. Regarding the genetic information, each thyroid cancer patient can be considered as an individual unique one, with unique genetic information. Contrary to standard chemotherapy drugs, target therapy components aim at one or more definite molecular pathway on cancer cells, so their selection is underlying patient’s genetic information. Nowadays, several mutations and rearrangements including BRAF, VEGF receptors, RET, and RET/PTC, KDR, KIT, PDGFRA, CD274, and JAK2 are taken into account for the therapeutic components like larotrectinib (TRK inhibitor), vemurafenib, sunitinib, sorafenib, selumetinib, and axitinib. With the new concept of personalized treatment of thyroid cancer diagnoses, planning treatment, finding out how well treatment will work, and estimating a prognosis has changed for the better over the last decade.Keywords: personalized medicine, target therapy, molecular testing